Analisis Faktor Tingkat Kepatuhan Minum Obat Pasien Diabetes Melitus di Puskesmas Pancoran Mas Periode Maret – April 2019 - Nadira Safa Jasmine; Sri Wahyuningsih; Maria Selvester Thadeus (Jurnal Manajemen Kesehatan Indonesia, 2020)
The prevalence of diabetes mellitus (DM) will continue to increase throughout the years. A way to achieve normal blood sugar levels is through adherence to medications. Nonadherence to medications in DM patients can result in high blood sugar levels and increase the risk of complications. This study was conducted to determine factors affecting medication adherence among DM patients in Puskesmas Pancoran Mas Depok in March – April 2019. This was an observational analytic study using a cross-sectional method. MMAS-8, DKQ-24 and family support questionnaires were used to collect the data along with the demographic data. Chi-square was used to analyze the data. The factors affecting medical adherence included patients’ education level (OR=2.325; 95%CI=1.034-5.224), gender (OR=4.200 95%CI=1.699-10.380), diabetes duration (OR = 2.426 95%CI=1.019-5.775), number of drugs taken (OR=3.680 95%CI=1.604-8.445), dosing frequency (OR=3.350 95%CI=1.283-8.749), and patient’s knowledge (OR=2.668 95%CI=1.135-6.276). Logistic regression analyzes showed that gender is the most powerful factors in affecting medication adherence.